2023
DOI: 10.1145/3563693
|View full text |Cite
|
Sign up to set email alerts
|

ThermoSecure: Investigating the Effectiveness of AI-Driven Thermal Attacks on Commonly Used Computer Keyboards

Abstract: Thermal cameras can reveal heat traces on user interfaces, such as keyboards. This can be exploited maliciously to infer sensitive input, such as passwords. While previous work considered thermal attacks that rely on visual inspection of simple image processing techniques, we show that attackers can perform more effective AI-driven attacks. We demonstrate this by presenting the development of ThermoSecure, and its evaluation in two user studies (N=21, N=16) which reveal novel insights about thermal attacks. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…automatically detect keyboards and key-presses in a thermal image [7,8]. This demonstration will display our current research, utilising the same automatic detection to create thermal cameras systems which obfuscate authentication interfaces, preventing thermal attacks as they happen and whether or not they were detected by the potential victim.…”
Section: Work By Alotaibi Et Al Has Demonstrated the Ability For A De...mentioning
confidence: 99%
See 2 more Smart Citations
“…automatically detect keyboards and key-presses in a thermal image [7,8]. This demonstration will display our current research, utilising the same automatic detection to create thermal cameras systems which obfuscate authentication interfaces, preventing thermal attacks as they happen and whether or not they were detected by the potential victim.…”
Section: Work By Alotaibi Et Al Has Demonstrated the Ability For A De...mentioning
confidence: 99%
“…First investigated in 2011 by Mowery [16], research in the years since have repeatedly found thermal imaging effective at conducting side-channel attacks on keyboards [8], keypads [14] and touchscreens [1]. Unlike shoulder surfing attacks which require real-time observation of user authentication, thermal attacks can be conducted in the window of time after the victim has entered their details and then left their device unattended, making them easier to perform.…”
Section: Motivation and Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Threat modeling is often defined as the formal process of identifying, documenting, and mitigating security threats to a system [20]. Human-centered threats involve social engineering attacks [15], shoulder surfing attacks [9,11], thermal attacks [1,2,5], smudge attacks [7,24], just to name a few. Designing authentication schemes against multiple threats is challenging, mainly because protecting users against all security and privacy threats is close to impossible [18].…”
Section: Threat Modeling In Usable Securitymentioning
confidence: 99%
“…Ref. [ 16 ] introduced AI-driven thermal attacks on commonly used computer keyboards. However, this attack technique has a limitation in that it requires thermal cameras.…”
Section: Introductionmentioning
confidence: 99%